2021
DOI: 10.1177/1078155221990101
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patient experience of telephone clinics implemented in light of COVID-19

Abstract: Introduction Due to the pandemic of COVID-19 a number of National Health Service (NHS) Trusts in the UK adopted telephone consultations for patients who were shielding. As the pandemic continues to affect these services an evaluation was conducted to determine whether telephone consultations implemented during the pandemic should be maintained long term. The objective was to evaluate this new service and to understand patient experience. Methods This study was conducted via a telephone survey. Staff working in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…In contrast to previous reviews which focused on usability, acceptance, engagement or effectiveness (Boulley et al, 2018;Cho et al, 2021;Slev et al, 2016;Triberti et al, 2019;Xu et al, 2019), we explored the personal experience detailed in studies to date of what it was like using technology. This review emphasizes the varied experiences regarding incorporating eHealth technology into everyday life, with views ranging of it being disruptive and time-consuming (Fergus et al, 2014;MacDonald et al, 2020;Martin et al, 2021) to barrier-defying in accessing necessary care (Dalby et al, 2021;Ownsworth et al, 2020). A unique aspect of this review is its focus on the family caregivers' experience of eHealth technology, either of dyadic interventions or their benefits related to their relative with cancer's use of supportive eHealth technology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous reviews which focused on usability, acceptance, engagement or effectiveness (Boulley et al, 2018;Cho et al, 2021;Slev et al, 2016;Triberti et al, 2019;Xu et al, 2019), we explored the personal experience detailed in studies to date of what it was like using technology. This review emphasizes the varied experiences regarding incorporating eHealth technology into everyday life, with views ranging of it being disruptive and time-consuming (Fergus et al, 2014;MacDonald et al, 2020;Martin et al, 2021) to barrier-defying in accessing necessary care (Dalby et al, 2021;Ownsworth et al, 2020). A unique aspect of this review is its focus on the family caregivers' experience of eHealth technology, either of dyadic interventions or their benefits related to their relative with cancer's use of supportive eHealth technology.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies found that technology was easily embedded in their daily routine and personal schedule (Maguire et al, 2020;Ngo et al, 2020;Hauffman et al, 2020), appreciating the option to engage at a time and pace that suited them (Song et al, 2015;Smith et al, 2020a;Drott et al, 2016) and enabled the person with cancer to plan their schedule (Mohsen et al, 2021;Crafoord et al, 2020). Participants with cancer also found benefit from eHealth technology in that they gained time in their own lives and did not have to travel to their treatment centre for supportive care, whereby people with cancer perceived an additionalreduced burden on their family caregivers (Dalby et al, 2021;Ownsworth et al, 2020).…”
Section: Alignment and Integration Of Ehealth Technology Into Daily Lifementioning
confidence: 99%
See 2 more Smart Citations
“…14 As such, there have been limited data on the efficacy of telemedicine for cancer care across the domains of consultation, treatment, and survivorship. 4,7,[15][16][17] The COVID-19 pandemic led to widespread public health measures, including the use of lockdowns and restricted access to medical facilities. These measures, in combination with concerns regarding disease spread, resulted in sharp increases in the use of telemedicine across many medical disciplines.…”
Section: Introductionmentioning
confidence: 99%